Thromboembolic acute myocardial infarction after aortic valve replacement using the Freestyle stentless aortic bioprosthesis with subcoronary valve replacement. (10th August 2018) - Watanabe, Yusuke; Naganuma, Toru; Kitanaka, Yosuke; Nakamura, Sunao
Abstract: A 70-year-old woman with substernal chest pain lasting 2.5 h presented to the emergency department of our hospital. She had a history of aortic valve replacement with the Freestyle stentless aortic bioprosthesis for severe aortic regurgitation 7 years ago. The initial electrocardiogram showed sinus rhythm at a rate of 71 bpm with ST-segment slight elevation in leads II, III and aVF. She was diagnosed as having acute coronary syndrome and was referred for an urgent catheterization. Urgent coronary angiography revealed total occlusion in the distal segment of the right coronary artery. Furthermore, a cavity was revealed around the aortic annulus by the contrast leaked from the ostium of the right coronary artery during angiography. Contrast-enhanced computed tomography showed an enhanced cavity between the native aortic wall and the bioprosthesis and the defect in the cavity. We diagnosed the incompetence of the bioprosthesis and decided to perform repeat aortic valve replacement. During surgery, the presence of a thrombus was confirmed in the cavity. The finding indicated that this embolic event was due to the thrombus from the cavity.